2014
DOI: 10.1021/es504253w
|View full text |Cite
|
Sign up to set email alerts
|

PCDD/PCDF Ratio in the Precursor Formation Model over CuO Surface

Abstract: The discrepancies between polychlorinated dibenzo-p-dioxin to polychlorinated dibenzofuran (PCDD to PCDF) ratios in laboratory and field studies in the exhaust of combustion sources are not fully explained by available formation models. In this paper we present the results of experimental studies of the surface mediated formation of PCDD/F at the conditions mimicking the combustion cool zone from a mixture of 1,2-dichlorobenzene (1,2-DCBz) and 2-monochlorophenol (2-MCP) over a model surface consisting of 5% Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…The same proportions of CBz, CPh and PCDD/F were detected during experiments using 1,2-DCBz as a precursor over copper and iron oxide systems (Nganai et al, 2014, 2012). This leads to the following assumption: is it possible that de novo formation as described in Figure 6 pays no contribution to the overall PCDD/F emission?…”
Section: Study Implications – Precursor Vs De Novosupporting
confidence: 55%
See 2 more Smart Citations
“…The same proportions of CBz, CPh and PCDD/F were detected during experiments using 1,2-DCBz as a precursor over copper and iron oxide systems (Nganai et al, 2014, 2012). This leads to the following assumption: is it possible that de novo formation as described in Figure 6 pays no contribution to the overall PCDD/F emission?…”
Section: Study Implications – Precursor Vs De Novosupporting
confidence: 55%
“…Figure 5 presents the integrated average yields of PCDD/F for the mixtures of 2-MCP and 1,2-DCBz and, for comparison, data published before for PCDD/F formation over CuO surfaces, determined at the same experimental conditions (Nganai et al, 2014). Based on Figure 5, it is apparent that with decreasing 2-MCP content in the feed stream, the PCDF formation yield is increasing and the plateau at the level of ~0.4% for pyrolytic and ~0.6% for oxidative conditions.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The emission limit and measurement method for PCDD/F emissions from MSW incineration has been established in many countries with developed environmental monitoring programs [22][23][24][25][26][27][28][29][30][31]. As can be seen in Table 1, most of the regulation standards just require measurements of PCDD/F emissions one or two times per year, e.g., at least once a year in China [24] and Japan [28].…”
Section: Requirement Of Fast Measurement Of Pcdd/fsmentioning
confidence: 99%
“…Since Öberg et al reported the correlations of hexachlorobenzene with TeCDD, PeCDD and PeCDF [37] and stated that PCDD/Fs could be predicted from chlorinated benzenes and phenols [38], PCDD/F indicators have been an active research topic [22,35,[39][40][41][42][43][44][45][46][47][48]. Prior indicators studied can be divided into 6 categories: CO, THC (total hydrocarbons), specific PCDD/F congeners, PAHs (polycyclic aromatic hydrocarbons), chlorophenols and chlorobenzenes.…”
Section: Pcdd/f Indicatorsmentioning
confidence: 99%